Design Process and Hydrodynamic Analysis of Underwater Remotely Operated Crawler - Zainal, Iktisyam; Mohd Shahrieel, Mohd Aras; Muhammad Nizam , Kamarudin; Harun, Mohamad Haniff; Mohd Khairi , Mohd Zambri; Alias , Khamis; Anuar , Mohamed Kassim (Penerbit Universiti, UTeM, 2016)
Underwater Remotely Operated Crawler (ROC) is a type of underwater Remotely Operated Vehicle (ROV) that able to operate underwater and even on land. The distinctive design of the ROC compared to other underwater vehicle is, ROC allows for underwater intervention by staying direct contact with the seabed. The common issues faced by all underwater vehicles are the drag that occurs when the vehicles move underwater. It is important to reduce the drag in order to increase the speed of the ROC with less power consumption. As such, the study of hydrodynamics to the ROC is essential so that the stability and maneuverability of the ROC can be guaranteed. SolidWorks software is used to design and analyses the ROC. The dimension of the ROC is 100-mm high, 449.60-mm long and 297.60 width. The body or chassis of the ROC is made of stainless steel. Based on the design and the capability of the ROC, it is estimated that the ROC can operate with less drag, withstand the underwater forces and stable to operate on the seabed.